PENGKAJIAN KARAKTERISTIK BAHAN BAKU (RAW MATERIAL) LEMBARAN BAJA (STEEL PLATE) UNTUK TABUNG GAS 3KG PRODUK LOKAL & IMPOR SECARA METALURGI - Winarto Winarto; Johny Wahyuadi s (JURNAL STANDARDISASI, 2008)
Nowadays, use of steel sheet material for gas tube 3kg in gas tube manufacture industry is increase in order tosupport governmental program about conversion of energy from kerosene to gas (LPG). Characteristic whichqualify for material of gas tube have been arranged in SNI 1452:2007 or JIS G3116 SG295 (standard of Japan).In JIS standard, it is arranged quality of raw material to be used in gas tube application steel like chemicalcomposition and tensile test. In other side production of local gas tube manufacturer is limited, while demand ofgas tube is increased, that’s why government gives opportunity to import tube of LPG 3kg. Meanwhile control ofraw material quality (steel plate) paid less attention so there are much gas tube damage like leaking and burstingin using. Therefore the study of raw material characteristic done to produce gas tube 3kg for both local and importproduct in metallurgy. The tests taken are tensile test, elongation, micro structure. This study aim to compare andanalyze the product in the metallurgy & valid standard in Indonesia, that is harmonies to Standard of IndonesiaNational (SNI) 1452:2007 and Japan Industrial Standard (JIS) G3116 SG295.